Response characteristics and particle contributions of epoxy resin composite embedded with Al particles under different loading modes - Zhenhui He; Enling Tang; Wenjin Yao; Ruizhi Wang (Journal of Materials Research and Technology)
Particle reinforced epoxy resin composites are widely used in aerospace, military defense, electronics industry and other fields because their mechanical strength, electromagnetic shielding effect and thermal stability can be controlled by adding different forms of particles. In this study, the universal testing machine and split hopkinson pressure bar were used to study the mechanical response and load distribution of Al particles embedded in epoxy resin composites with different volume fractions under various loading modes by combining theoretical derivation and digital image technology. The contribution of Al particles to its mechanical properties was quantitatively analyzed. Research results show that the epoxy resin primarily serves as the load-bearing matrix under tension conditions. When the Al particle content is below 10 vol%, the overall mechanical properties of the epoxy/Al composite are similar to epoxy resin. Under compression conditions, as the force vectors on the Al particles always align with the loading direction, the load at this time exhibits an additive effect of the epoxy resin and Al particles in the loading direction. The load-bearing matrix gradually transitions to the epoxy resin matrix with the continuous increase of Al particle content. At the loading speed of 20 m/s, the load bearing carrier gradually changed into epoxy resin matrix with the increase of Al particle content. The strength of epoxy/Al material added with 50 vol% Al particles is up to 322.44 MPa, which is 3.78 times that of pure epoxy resin material. The load-carrying efficiency of epoxy/Al composite materials in the principal stress direction depends on the particle chain length and coaxiality. The shear load-carrying carrying efficiency is determined by the particle stacking situation, and the larger the stacking area, the higher the tangential carrying efficiency. As the Al particle content increases, the unit particle potential energy shows a trend of decreasing first and then increasing. When the Al particle content is 15 vol%, the particle potential energy is 1.25 MJ/m³ and at its lowest. However, when the volume fraction of Al particles reaches 50 vol%, the particle potential energy is at its highest, reaching 6.62 MJ/m³.